2015
DOI: 10.3892/or.2015.4099
|View full text |Cite
|
Sign up to set email alerts
|

miR-130a acts as a potential diagnostic biomarker and promotes gastric cancer migration, invasion and proliferation by targeting RUNX3

Abstract: MicroRNAs (miRNAs) are abnormally expressed in various types of cancer. miR-130a expression and function in gastric cancer has yet to be elucidated. The aim of the present study was to identify the miR-130a expression and function in gastric cancer. miR-130a expression was examined in gastric cancer cell lines and tissues by RT-qPCR. The diagnostic and prognostic significance of miR-130a in gastric cancer was analyzed by receiver-operating characteristic (ROC) curve and Kaplan-Meier analysis. miR130a expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 41 publications
3
56
2
Order By: Relevance
“…miRNAs have important roles in regulating a number of cell processes, including cell differentiation, apoptosis and cell cycle progression (5)(6)(7)(8)(9). miRNAs serve as biomarkers in various types of cancer, including GC and prostate cancer (10,11). Although a number of miRNAs have been identified to be dysregulated in GC tissues, the role of miR-1258 in GC has not, to the best of our knowledge, previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have important roles in regulating a number of cell processes, including cell differentiation, apoptosis and cell cycle progression (5)(6)(7)(8)(9). miRNAs serve as biomarkers in various types of cancer, including GC and prostate cancer (10,11). Although a number of miRNAs have been identified to be dysregulated in GC tissues, the role of miR-1258 in GC has not, to the best of our knowledge, previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that miRNAs may be used as molecular biomarkers in the diagnosis and prognosis of GC (10)(11)(12). Oncogenic miRNAs, which are generally upregulated in GC, exert their function by silencing the expression of genes that inhibit the cell cycle and/or genes associated with apoptotic pathways (13)(14)(15). By contrast, miRNAs that are downregulated act as tumor suppressors during GC progression.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, miRNAs that are downregulated act as tumor suppressors during GC progression. These miRNAs generally exert their function via anti-proliferative and pro-apoptotic associated genes (14)(15)(16). Additionally, decreased levels of miR-144 in GC tissue may be associated with poor patient prognosis and it was demonstrated that the reintroduction of miR-144 increased the susceptibility of cancer cells to chemotherapy (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that miR-130a is associated with lung cancer [50], gastric cancer [51,52], ovarian cancer [53][54][55][56][57], cervical cancer [58,59], and prostate cancer [60]. Recently, deep sequencing technology was used to identify differentially expressed host miRNAs in chickens [28,34,35,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that miR-130a modulates vascular smooth muscle cell proliferation under hypertension [63]. In addition, miR-130a promots cell proliferation and migration by targeting RUNX3 (runt-related transcription factor 3) in gastric cancer [51]. In human breast cancer, miR-130a was found to inhibit cell proliferation and migration by targeting RAB5A (member RAS oncogene family) [64].…”
Section: Discussionmentioning
confidence: 99%